2020
DOI: 10.1177/0300985820908792
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic Feline Mammary Carcinomas Including Carcinoma and Malignant Myoepithelioma

Abstract: Feline mammary tumors are usually malignant and aggressive carcinomas. Most cases are simple monophasic carcinomas (1 epithelial population), and additional phenotyping is usually not needed. In this study, we describe 10 malignant mammary tumors from 9 female cats that had unusual histomorphology: they appeared biphasic, with 2 distinct cell populations. Initially, they were morphologically diagnosed as either carcinosarcoma (1/10) or malignant pleomorphic tumor (9/10) of the mammary gland, as the latter did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 58 publications
4
5
0
1
Order By: Relevance
“…Unlike the results ofMorris (2013); Mills et al (2015) andCassali et al (2018) that reported lobular hyperplasia and duct ectasia as a single lesions. Many of our cases showed those changes along with different patterns of malignant carcinomas.In agreement with Mills et al(2015);Sammarco et al (2020) andChen et al (2020), FMT were usually associated with intense stromal fibrosis (scirrhous reaction) while,…”
supporting
confidence: 88%
See 3 more Smart Citations
“…Unlike the results ofMorris (2013); Mills et al (2015) andCassali et al (2018) that reported lobular hyperplasia and duct ectasia as a single lesions. Many of our cases showed those changes along with different patterns of malignant carcinomas.In agreement with Mills et al(2015);Sammarco et al (2020) andChen et al (2020), FMT were usually associated with intense stromal fibrosis (scirrhous reaction) while,…”
supporting
confidence: 88%
“…As previously described by Sammarco et al (2020), presence of biphasic FMT not a quite common finding that could not be distinguished easily by histologic examination, in our results a case of proliferating pleomorphic population of vimentin positive myoepithelial cells was reported. Glycogen-rich carcinoma with its described histologic patterns was similar to that reported in a Persian queen by Campos et al (2016).…”
Section: Whole Slide Images (Wsi) Examinationsupporting
confidence: 63%
See 2 more Smart Citations
“…The availability of anti-human PR antibodies cross-reacting in animal tissues is, at the moment, an unsolved issue. Previously cross-reacting antibodies are no longer commercially available and those tested did not give robust results after several attempted protocols [16,41,42,[44][45][46].…”
Section: Discussionmentioning
confidence: 99%